A Clinicopathological Profile of Prostate Cancer in Trinidad and Tobago - Ian Hosein; Rajendra Sukhraj; Lester Goetz; Nastassia Rambarran; Satyendra Persaud (Advances in Urology)
Aim. To conduct a clinicopathological review of all prostate biopsies performed in a tertiary referral centre in Trinidad and Tobago over a period of 30 months. Methods. The records of all patients who had prostate biopsies from January 2012 to July 2014 were reviewed. Clinical and pathologic data were compiled and subsequently analysed using SPSS version 20. Results. From January 2012 to July 2014, 617 transrectal ultrasound guided prostate biopsies were performed. Pathological data were found for 546 patients of whom 283 (51.8%) were confirmed carcinoma of the prostate. Moderately differentiated tumors (Gleason 7) were the most common group. Using the D’Amico risk classification, most cases were found to be high risk (63.1%). Afro-Trinidadians comprised 72.1% of the patients with prostate cancer. Afro-Trinidadians were also more likely to have high risk and high grade disease as well as high PSA values. Conclusion. This study demonstrates that over half of our biopsies are eventually positive for cancer and most cases were high risk. Afro-Trinidadians comprised a disproportionate number of those diagnosed with prostate cancer and had a greater risk of high risk disease.